Genome-wide identification and structure-function studies of proteases and protease inhibitors in cicer arietinum (chickpea) - Sharma, Ranu; Suresh, C. G. (Computers in Biology and Medicine, 2015)
Background: Proteases are a family of enzymes present in almost all living organisms. In plants they are involved in many biological processes requiring stress response in situations such as water deficiency, pathogen attack, maintaining protein content of the cell, programmed cell death, senescence, reproduction and many more. Similarly, protease inhibitors (PIs) are involved in various important functions like suppression of invasion by pathogenic nematodes, inhibition of spores-germination and mycelium growth of Alternaria alternata and response to wounding and fungal attack. As much as we know, no genome-wide study of proteases together with proteinaceous PIs is reported in any of the sequenced genomes till now. Methods: Phylogenetic studies and domain analysis of proteases were carried out to understand the molecular evolution as well as gene and protein features. Structural analysis was carried out to explore the binding mode and affinity of PIs for cognate proteases and prolyl oligopeptidase protease with inhibitor ligand. Results: In the study reported here, a significant number of proteases and PIs were identified in chickpea genome. The gene expression profiles of proteases and Pis in five different plant tissues revealed a differential expression pattern in more than one plant tissue. Molecular dynamics studies revealed the formation of stable complex owing to increased number of protein-ligand and inter and intramolecular protein-protein hydrogen bonds. Discussion: The genome-wide identification, characterization, evolutionary understanding, gene expression, and structural analysis of proteases and Pis provide a framework for future analysis when defining their roles in stress response and developing a more stress tolerant variety of chickpea. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Domain; Gene expression; Genome analysis; Homology modelling; Molecular docking; molecular dynamics simulation; Motif; Orthologs; Phylogeny